Cecal Patches Generate Abundant IgG2b-Bearing B Cells That Are Reactive to Commensal Microbiota - Masato Tsuda; Hiraku Okada; Natsuki Kojima; Fumiya Ishihama; Yuhei Muraki; Toshiki Oguma; Nanako Hattori; Takumi Mizoguchi; Kiyoaki Mori; Satoshi Hachimura; Yoshimasa Takahashi; Kyoko Takahashi; et al. (Journal of Immunology Research)
Gut-associated lymphoid tissue (GALT), such as Peyer’s patches (PPs), are key inductive sites that generate IgA+ B cells, mainly through germinal center (GC) responses. The generation of IgA+ B cells is promoted by the presence of gut microbiota and dietary antigens. However, the function of GALT in the large intestine, such as cecal patches (CePs) and colonic patches (CoPs), and their regulatory mechanisms remain largely unknown. In this study, we demonstrate that the CePs possess more IgG2b+ B cells and have fewer IgA+ B cells than those in PPs from BALB/c mice with normal gut microbiota. Gene expression analysis of postswitched transcripts supported the differential expression of dominant antibody isotypes in B cells in GALT. Germ-free (GF) mice showed diminished GC B cells and had few IgA+ or IgG2b+ switched B cells in both the small and large intestinal GALT. In contrast, myeloid differentiation factor 88- (MyD88-) deficient mice exhibited decreased GC B cells and presented with reduced numbers of IgG2b+ B cells in CePs but not in PPs. Using ex vivo cell culture, we showed that CePs have a greater capacity to produce total and microbiota-reactive IgG2b, in addition to microbiota-reactive IgA, than the PPs. In line with the frequency of GC B cells and IgG2b+ B cells in CePs, there was a decrease in the levels of microbiota-reactive IgG2b and IgA in the serum of GF and MyD88-deficient mice. These data suggest that CePs have a different antibody production profile compared to PPs. Furthermore, the innate immune signals derived from gut microbiota are crucial for generating the IgG2b antibodies in CePs.